Book Review Papers in Language Related Journals: How Authors Evaluate and Promote the Books Under Review - Juansyah, Mardi; Arsyad, Safnil; Whardana, Dian Eka Chandra; Annur, Yusri Fajri (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
Writing a research article for a reputable journal is not easy especially for new authors or postgraduate students in social sciences and humanities including language related fields but they can write and publish a book review paper (henceforth BRP) in a high impact journal to practice writing in English at an advanced level. This study is aimed at analyzing the discourse structure and argument style of BRPs in language related fields published in high impact journals. Sixty BRPs were chosen from six different journals published in several countries analyzed in this research. The four move BRP discourse pattern model as suggested by Bezerra (2001) was used in this study. The results show that, in terms of the appearance of moves: Move 1 or introducing the book and Move 4 or addressing a final idea about the book are categorized as conventional while Move 2 or outlining the book content and Move 3 or examining the book are obligatory. However, only one step (Move 2-Step B or highlighting the topic of the book) out of 16 steps in all moves is obligatory; 7 steps are classified as conventional and the other 8 are optional. In other words, in each move, there is at least one obligatory or conventional step. This implies that only a half or 50% of the steps are obligatory or conventional while the other half are optional. The optional steps are possibly used by the BRP authors to provide additional important information about the book being reviewed to attract readers to read and/or own the book.